2022
DOI: 10.3390/ijms23169314
|View full text |Cite
|
Sign up to set email alerts
|

CXCL14 Attenuates Triple-Negative Breast Cancer Progression by Regulating Immune Profiles of the Tumor Microenvironment in a T Cell-Dependent Manner

Abstract: Triple-negative breast cancer (TNBC) is aggressive and has a poor overall survival due to a lack of therapeutic targets compared to other subtypes. Chemokine signature revealed that TNBC had low levels of CXCL14, an orphan homeostatic chemokine to regulate the immune network. Here, we investigated if CXCL14 plays a critical role in TNBC progression, focusing on survival rates, tumor growth and metastasis, and immune profiles in the tumor microenvironment. Analysis of human breast-cancer datasets showed that lo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 44 publications
0
2
0
Order By: Relevance
“…Indeed, CXCL14 has been reported to participate in mediating immune profiles in breast cancer, glioma, and sarcoma. 21,41,42 In glioma, CXCL14 promoted directional migration and chemotaxis of activated CD8+ T cells in a dose-dependent way in vitro. In vivo, CXCL14 was associated with prolonged survival in a CD8+ T-cell-dependent manner.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, CXCL14 has been reported to participate in mediating immune profiles in breast cancer, glioma, and sarcoma. 21,41,42 In glioma, CXCL14 promoted directional migration and chemotaxis of activated CD8+ T cells in a dose-dependent way in vitro. In vivo, CXCL14 was associated with prolonged survival in a CD8+ T-cell-dependent manner.…”
Section: Discussionmentioning
confidence: 99%
“…Increasing the proportion of M1-type macrophages is an important indicator of good prognosis in cancer [14,15]. Although CXCL14 is a relatively novel gene in the chemokine family, it has long been reported that CXCL14 is closely related to the occurrence of breast cancer, liver cancer, lung cancer and other cancers [16][17][18][19][20][21][22]. It has been found that CXCL14 is significantly downregulated in HPV-positive head/neck cancer and cervical tissue specimens, and restoring the expression of CXCL14 in oropharyngeal cancer cells could clear tumors in mice [23].…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, the aggressive TNBC phenotype has been associated with epigenetic modulation, calcium signaling, and the loss of MHC I [ 9 , 10 , 11 ]. Currently, attenuation of TNBC progression by modulating the cancer signaling pathways such as by inhibiting CDK14, induction of chemokines such as CXCL14, and inhibition of NF-κB is promising [ 12 , 13 , 14 ]. The NF-κB pathway is highly associated with BC, as shown by its inhibition via parthenolide that inhibits TNBC progression, inducing apoptosis in mammary tumors, enhancing chemo-sensitivity in BC cells, and suppressing metastatic markers in TNBC [ 15 , 16 , 17 , 18 ].…”
Section: Introductionmentioning
confidence: 99%